Production of lambda(+)(c) baryons in proton-proton and lead-lead collisions at root S-NN=5.02 TeV - KAYA, MİTHAT (My University, 2020)
The transverse momentum (P-T) spectra of inclusively produced A c P baryons are measured via the exclusive decay channel Lambda(+)(c) -> pK(-)pi(+) using the CMS detector at the LHC. Spectra are measured as a function of transverse momentum in proton-proton (pp) and lead-lead (PbPb) collisions at a nucleonnucleon center-of-mass energy of 5.02TeV. The measurement is performed within the Lambda(+)(c) rapidity interval vertical bar Y vertical bar < 1 in the p(T) range of 5-20GeV/c in pp and 10-20GeV/c in PbPb collisions. The observed yields of Lambda(+)(c) for p(T) of 10-20 GeV/c suggest a suppression in central PbPb collisions compared to pp collisions scaled by the number of nucleon-nucleon (NN) interactions. The Lambda(+)(c)/D-0 production ratio in pp collisions is compared to theoretical models. In PbPb collisions, this ratio is consistent with the result from pp collisions in their common p-r range. (C) 2020 The Author(s). Published by Elsevier B.V.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Parçacıklar ve Alanlar; Temel Bilimler; Physics; Astronomy and Astrophysics; Basic Particles and Areas; Natural Sciences; ASTRONOMİ VE ASTROFİZİK; Uzay bilimi; Temel Bilimler (SCI); FİZİK, NÜKLEER; FİZİK, PARÇACIKLAR VE ALANLAR; ASTRONOMY & ASTROPHYSICS; SPACE SCIENCE; Natural Sciences (SCI); PHYSICS, NUCLEAR; PHYSICS; PHYSICS, PARTICLES & FIELDS; Nükleer ve Yüksek Enerji Fiziği; Fizik ve Astronomi (çeşitli); Genel Fizik ve Astronomi; Uzay ve Gezegen Bilimi; Fizik Bilimleri; Nuclear and High Energy Physics; Physics and Astronomy (miscellaneous); General Physics and Astronomy; Space and Planetary Science; Physical Sciences; CMS; Lambda(c) baryons; Nuclear modification factor; Heavy flavor; PB-PB COLLISIONS; J/PSI SUPPRESSION; RAPIDITY; Physics; Lambda(c) baryons; Nuclear modification factor; Heavy flavor